Autophagy in chronic rhinosinusitis with or without nasal polyps - Pei, Jing; Ding, Zhaoran; Jiao, Cheng; Tao, Ying; Yang, Huifen; Li, Jing (Frontiers in Cell and Developmental Biology, 2024)
Basic research on chronic rhinosinusitis (CRS) has advanced significantly in the past two decades, yet a comprehensive understanding of its pathogenic mechanisms remains elusive. Concurrently, there is a growing interest among scientists in exploring the involvement of autophagy in various human diseases, including tumors and inflammatory conditions. While the role of autophagy in asthma has been extensively studied in airway inflammatory diseases, its significance in CRS with or without nasal polyps (NPs), a condition closely linked to asthma pathophysiology, has also garnered attention, albeit with conflicting findings across studies. This review delves into the role of autophagy in CRS, suggesting that modulating autophagy to regulate inflammatory responses could potentially serve as a novel therapeutic target (Figure 1).